Breast MRI in Invasive Lobular Carcinoma: A Useful Investigation in Surgical Planning?. Issue 2 (3rd February 2016) - Parvaiz, Muhammad Asad; Yang, Peiming; Razia, Eisha; Mascarenhas, Margaret; Deacon, Caroline; Matey, Pilar; Isgar, Brian; Sircar, Tapan
Abstract: Magnetic resonance imaging (MRI) is highly sensitive in detecting invasive lobular carcinoma (ILC) of the breast. In our institution, patients who are deemed to be suitable for breast conserving surgery (BCS) with unifocal small ILC on standard imaging are offered breast MRI to exclude multifocal and larger ILC. Our study investigates the usefulness of breast MRI in ILC. A prospective cohort study over a 58‐month period, including all consecutive patients with ILC having breast MRI. Primary objective was to find out the proportion of ILC patients where preoperative MRI caused a change in the surgical treatment. Secondary objectives included finding mastectomy rate (initial & final), re‐operation rate, cancer size correlation with different imaging modalities and final histopatholgy, loco‐regional recurrence and disease‐free survival. A total of 334 bilateral breast MRI were performed including 72 (21.5%) MRI for ILC patients. All these MRI were carried out within 2 week of patients given the diagnosis (median 5.5 days). Age range was 24–83 (median 56.5) years. Nineteen of 72 ILC patients (26.4%) had a change in their planned operation from BCS to a different operation owing to MRI findings (seven patients with multifocal cancers, 10 with significantly larger size of the cancer and two with contralateral malignancy). Initial mastectomy rate was 31.9%, final mastectomy rate was 36.1% and re‐operation rate in BCS group was 18.3%. MRI correlated better with ILC histopathology cancer size than mammogram and ultrasound scans. There was no statistically significant difference (p = 0.999) between the cancer size on histology (median 23 mm) and MRI (median 25 mm). However, mammogram (median 17 mm) and ultrasound (median 14.5 mm) scans showed cancer sizes significantly different to final histology cancer size (p = 0.0008 and p = 0.0021 respectively). Over a 44 months median follow‐up (range 27–85), 95.8% disease‐free survival and 98.6% overall survival have been observed. One out of every four patients (26.4%) with ILC had a change in their planned operation due to MRI findings. A relatively high disease‐free survival over a medium‐term follow‐up proves the oncological safety of MRI in ILC. Our study provides evidence in support of the targeted use of preoperative breast MRI among patients with ILC to improve surgical planning.